Targeting the leptin receptor promotes MDA-MB-231 cells’ metabolic reprogramming and malignancy: the role of extracellular vesicles derived from obese adipose tissue - Encarnação, Carol Costa; Amorim, Carolinne Souza; Franco, Victor Aguiar; Botelho, Luiz Gabriel Xavier; dos Santos, Ronan Christian Machado; Ramos-Andrade, Isadora; Kraemer-Aguiar, Luiz Guilherme; Barja-Fidalgo, Christina; Moraes, João Alfredo; Renovato-Martins, Mariana (Frontiers in Oncology, 2025)
IntroductionLeptin, a key adipokine secreted by adipose tissue (AT), has emerged as a critical mediator linking obesity and breast cancer, both of which are major global health concerns. Elevated leptin levels are detected in the circulation and in extracellular vesicles (EVs) released by adipose tissue, particularly in cases of obesity. These leptin-enriched EVs have been implicated in various stages of tumor progression. In this study, we investigated the effects of leptin within extracellular vesicles (EVs) secreted by obese adipose tissue on the functional properties and metabolism of MDA-MB-231 breast cancer cells, a model for triple-negative breast cancer (TNBC).MethodMDA-MB-231 cells were treated with EVs derived from the subcutaneous adipose tissue of eutrophic (EUT EVs) and obese (OB EVs) individuals.ResultsOur findings revealed that OB EVs induced significant phosphorylation of STAT3, a key signaling molecule in cancer progression, and promoted increased cell migration, dependent on fatty acid oxidation (FAO). This effect was reversed in the presence of a leptin receptor antagonist, highlighting leptin’s pivotal role in these processes. Additionally, OB EVs caused metabolic changes, including reduced lactate levels and decreased pyruvate kinase (PK) activity, while increasing glucose-6-phosphate dehydrogenase (G6PDH) activity, suggesting metabolic reprogramming that supports tumor cell survival and proliferation. In addition to metabolic alterations, OB EVs also impacted mitochondrial dynamics. We observed an upregulation of fusion and fission markers and a redistribution of mitochondria toward the cell periphery, which supports migration. Moreover, OB EVs increased the invasive capacity of MDA-MB-231 cells, an effect mediated by matrix metalloproteinase-9 (MMP-9).DiscussionOverall, our results highlight how obese adipose tissue modulates breast cancer cell behavior, with leptin-enriched EVs playing a central role in driving migration, metabolic reprogramming, and invasiveness, thereby promoting tumor malignancy. This study underscores the importance of EVs in the obesity-cancer link and offers new insights for therapeutic strategies targeting leptin signaling and EV-mediated communication in breast cancer.